Creation at risk? : religion, science, and environmentalism - Cromartie, Michael; Derr, Thomas Sieger, 1931- (Ethics and Public Policy Center ; W.B. Eerdmans Pub. Co, 1995)
The environmental movement both echoes and challenges traditional Judeo-Christian views about humankind's proper relationship to the natural world. Ten scholars and activists here explore - and clash over - some of the scientific, religious, moral, philosophical, economic, and political claims advanced by contemporary environmentalists.